Extracellular DNA of slow growers of mycobacteria and its contribution to biofilm formation and drug tolerance - Aleksandr Ilinov (Nature Portfolio, 2021)
Abstract DNA is basically an intracellular molecule that stores genetic information and carries instructions for growth and reproduction in all cellular organisms. However, in some bacteria, DNA has additional roles outside the cells as extracellular DNA (eDNA), which is an essential component of biofilm formation and hence antibiotic tolerance. Mycobacteria include life-threating human pathogens, most of which are slow growers. However, little is known about the nature of pathogenic mycobacteria’s eDNA. Here we found that eDNA is present in slow-growing mycobacterial pathogens, such as Mycobacterium tuberculosis, M. intracellulare, and M. avium at exponential growth phase. In contrast, eDNA is little in all tested rapid-growing mycobacteria. The physiological impact of disrupted eDNA on slow-growing mycobacteria include reduced pellicle formation, floating biofilm, and enhanced susceptibility to isoniazid and amikacin. Isolation and sequencing of eDNA revealed that it is identical to the genomic DNA in M. tuberculosis and M. intracellulare. In contrast, accumulation of phage DNA in eDNA of M. avium, suggests that the DNA released differs among mycobacterial species. Our data show important functions of eDNA necessary for biofilm formation and drug tolerance in slow-growing mycobacteria.